The Dynamic response of shallow sandwich arch with auxetic metallic honeycomb core under localized impulsive loading - Li, Ying; Chen, Zihao; Xiao, Dengbao; Wu, Wenwang; Fang, Daining (International journal of impact engineering, 2020)
•The experimental and numerical methods were used to investigate the dynamic response of end-clamped shallow sandwich arch with HCNPR under local impulsive.•The local negative Poisson's ratio deformation was observed in the reentrant honeycomb core.•The dynamic deformation evolution of the face sheets and honeycomb core was studied. In recent years, auxetic metallic cellular material such as auxetic reentrant honeycomb is one of the research hotspot in metallic cellular materials due to its attractively negative Poisson's ratio. In this manuscript, the dynamic response of the end-clamped shallow sandwich arch with aluminum face sheets and auxetic reentrant hexagonal aluminum honeycomb core subjected to foam projectile with high-velocity impact was experimentally and numerically investigated. The reentrant honeycomb cores with different cell-wall thicknesses were fabricated by selective laser melting (SLM). The deformation processes of honeycomb core were captured by a high-speed camera. And deflection history of back face sheet was obtained using three-dimensional digital imaging correlation method (DIC) analysis system. Failure modes and deformation mechanisms of the sandwich arch were investigated. According to experiment results, the local negative Poisson's ratio deformation was found in honeycomb core. Then, a finite element (FE) model was established to study the dynamic deformation evolution of two face sheets and auxetic reentrant honeycomb core. The results showed that the honeycomb cells were not always undergoing shrinkage deformation and flowing into the loading center, while the local expand deformations of honeycomb core were also found.